Fresh and brackish water ostracods of Upper Miocene deposits, Arguvan/Malatya (Eastern Anatolia) - Nazik, Atike; Turkmen, Ibrahim; Koc, Calibe; Aksoy, Ercan; Avsar, Niyazi; Yayik, Huelya (Tubitak Scientific & Technological Research Council Turkey, 2008)
The Neogene Alibonca, Kuseyin, Parcikan, Boyaca formations and the Mamaar volcanic unit occur at Arguvan (Malatya, Eastern Anatolia). Nine species of ostracods were identified and assigned to four genera in samples collected from the Kuseyin and Parcikan formations. The faunal content in these units was characterized by few ostracod species and abundant individuals. Most samples contained fewer than nine species. Ilyocypris bradyi, Ilyocypris gibba, Candona parallela pannonica and Heterocypris salina are described in the Kuseyin Formation. Cyprideis pannonica, Cyprideis anatolica, Cyprideis torosa, Ilyocypris gibba, Candona angulata, Candona neglecta, Candona parallela pannonica and Heterocypris salina are described in Parcikan Formation. Cyprideis, which has ecophenotypic ornamentations (smooth, punctuated, reticulated or nodes), is the dominant genus in the Parcikan Formation. Lithological features and fossil contents of the Upper Miocene units suggest that the Kuseyin Formation was deposited by a meandering river and the Parcikan Formation was formed in a shallow lacustrine environment associated with swamps. The ostracod assemblages have been correlated with ostracod species of the Tethys and Paratethys regions. Cyprideis pannonica is observed in the Paratethys and Tethys bioprovinces. Cyprideis torosa, Ilyocypris gibba, Ilyocypris bradyi, Heterocypris salina, Candona angulata, Candona neglecta Sars are known in Europe and the Tethys bioprovince.
Keywords: Neogene; Eastern Anatolia; Ostracoda; freshwater; brackish water